Efficacy of multisystemic therapy in youths aged 10-17 with severe antisocial behaviour and emotional disorders: systematic review - Tan, Jia Xuan; Fajardo, Maria Lourdes Restrepo (London journal of primary care, 2017)
Background: Antisocial behaviour and conduct disorders are the most common behavioural and mental health problems in children and young people globally. An efficacious intervention is needed to manage these antisocial behaviours that have costly consequences. Multisystemic Therapy (MST), an intensive home-based intervention for youths with psychosocial and behavioural problems, is recommended under National Institute for Health and Clinical Excellence guidelines for conduct disorder. However, reviews on the efficacy of MST are mixed. Aim: To review randomised controlled trials (RCTs) reporting efficacy of MST among youths presenting with antisocial behaviour and emotional disorder respectively. Method: A systematic map term to subject heading search was conducted in PsycINFO, Embase, and Ovid Medline databases for articles up to November 2015. RCTs comparing MST vs.treatment as usual (TAU) in youths presenting with antisocial behaviour and emotional disorder were included. Results: 12 RCTs (n = 1425) reported efficacy of MST vs. TAU in youths presenting with antisocial behaviour and emotional disorder. Clinically significant treatment effects of MST showed a reduction of antisocial behaviour which includes delinquency. MST, vs. psychiatric hospitalisation, was associated with a reduction of suicidal attempts in youths presenting with psychiatric emergencies. 4 studies showed that MST was less costly than TAU in the short term, with further analysis required for long-term cost-effectiveness. Conclusion: MST is an efficacious intervention for severe antisocial behaviours in reduction of delinquency and should be included in clinical practices. MST was shown to have a positive effect on emotional disorder but further research is needed to evaluate the efficacy of MST with emotional disorder. Further analysis is required to assess the services utilized for long-term cost effectiveness.